Estimating Above Ground Biomass using Remote Sensing in the Sub-Tropical Climate Zones of Australia - Mundava, Charity (Curtin University, 2015)
The study focused on assessing the total above ground biomass using remote sensing in the Kimberley rangelands of Western Australia. Remote sensing has the advantage that it can rapidly provide estimates non-destructively on a large scale with a high temporal frequency. In this thesis a field sampling protocol was developed and mono- and multi-temporal above ground biomass estimation models could be calibrated and validated with field based measurements for the most significant vegetation types.